Economic Analysis of a Silvo-pastoral System for Degraded Lands under Rainfed Condition - Kareemulla, K.; Rai, P.; Rao, G. R.; Solanki, K. R. (Indian Forester, 2002)
Degraded lands can be effectively nsed for producing forage, nutritious leaf fodder, fuel wood and timber with the introduction of silvopastoral system based on species like Albizia amara, Leucaena leucocephala, Dichrostachys cinerea (tree component); Chrysopogan fulvus, Stylosanthes hamata and S. scabra (pasture component). The biomass productivity of 7.13 t ha-1 year-1 was recorded. The discounted B:C ratio of this system worked out to 1:1.52.